Bacterial approaches to sensing and responding to respiration and respiration metabolites. Issue 4 (25th August 2021) - Price, Erin E.; Román‐Rodríguez, Franklin; Boyd, Jeffrey M.
Abstract: Bacterial respiration of diverse substrates is a primary contributor to the diversity of life. Respiration also drives alterations in the geosphere and tethers ecological nodes together. It provides organisms with a means to dissipate reductants and generate potential energy in the form of an electrochemical gradient. Mechanisms have evolved to sense flux through respiratory pathways and sense the altered concentrations of respiration substrates or byproducts. These genetic regulatory systems promote efficient utilization of respiration substrates, as well as fine‐tune metabolism to promote cellular fitness and negate the accumulation of toxic byproducts. Many bacteria can respire one or more chemicals, and these regulatory systems promote the prioritization of high‐energy metabolites. Herein, we focus on regulatory paradigms and discuss systems that sense the concentrations of respiration substrates and flux through respiratory pathways. This is a broad field of study, and therefore we focus on key fundamental and recent developments and highlight specific systems that capture the diversity of sensing mechanisms. Abstract : Respiration provides organisms with a means to dissipate reductants and generate potential energy in the form of an electrochemical gradient. Regulatory systems have evolved to promote efficient utilization of respiration substrates, as well as fine‐tune metabolism to promote cellular fitness and negate the accumulation of toxic byproducts. Herein, we discuss regulatory paradigms and systems that sense the concentrations of respiration substrates and flux through respiratory pathways.